Publisher correction: Sex-dimorphic genetic effects and novel loci for fasting glucose and insulin variability - Lagou, Vasiliki; Kleber, Marcus E.; März, Winfried (Nature Communications, 2021)
Correction to: Nature Communications https://doi.org/10.1038/s41467-020-19366-9, published online 5 January 2021. The original version of this Article contained an error in Fig. 2, in which panels a and b were inadvertently swapped. This has now been corrected in the PDF and HTML versions of the Article.
Vasilili, Lagou, Marcus E. Kleber, Winfried März & Meta-Analyses of Glucose and Insulin-related traits Consortium (MAGIC) [und viele weitere]
Gesehen am 17.05.2021